Risk of serious adverse events after primary shoulder replacement: development and external validation of a prediction model using linked national data from England and Denmark - Valsamis, EM; Jensen, ML; Coward, G; Sayers, A; Pinedo-Villanueva, R; Rasmussen, JV; Collins, GS; Rees, JL (Elsevier, 2024)
Background Despite a rising rate of serious medical complications after shoulder replacement surgery, there are no prediction models in widespread use to guide surgeons in identifying patients at high risk and to provide patients with personalised risk estimates to support shared decision making. Our aim was to develop and externally validate a prediction model for serious adverse events within 90 days of primary shoulder replacement surgery.